2017
DOI: 10.1002/aenm.201701601
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Porous Molybdenum Carbide and Phosphide Hybrids on a Carbon Matrix as Highly Effective Electrocatalysts for the Hydrogen Evolution Reaction

Abstract: Platinum (Pt) is the most active and stable HER catalyst, but its high cost and low abundance hinder its widespread applications. [3][4][5][6] Recently, tremendous efforts have been devoted to the search for noble-metal-free catalysts to replace Pt-based catalysts in the generation of H 2 with a high current density at a low overpotential. [7][8][9][10] In particularly, molybdenum carbides and molybdenum phosphides have been demonstrated as active and robust HER catalysts due to their high conductivities, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 233 publications
(135 citation statements)
references
References 56 publications
5
129
0
1
Order By: Relevance
“…In the equivalent circuit model, R s , R p , and R ct denote the solution, electrode porosity, and charge transfer resistances, respectively, whereas the CPE and C dl represent the constant phase element and double-layer capacitance, respectively. [45] The stability of the electrocatalysts at high current densities is one of the major concerns for large-scale practical applications. [46] In fact, the trend of R ct is in accord with those of η 10 , η 250 , η 500 , and Tafel slope.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the equivalent circuit model, R s , R p , and R ct denote the solution, electrode porosity, and charge transfer resistances, respectively, whereas the CPE and C dl represent the constant phase element and double-layer capacitance, respectively. [45] The stability of the electrocatalysts at high current densities is one of the major concerns for large-scale practical applications. [46] In fact, the trend of R ct is in accord with those of η 10 , η 250 , η 500 , and Tafel slope.…”
Section: Resultsmentioning
confidence: 99%
“…The HER kinetic characteristics of the NFN-MOF/NF and comparison electrodes were next studied with Tafel plots (Figure 3c). [45] The high current stability of the NFN-MOF/NF electrode toward the HER was next evaluated with chronoamperometric and chronopotentiometric measurements for 30 h at −250 and −500 mA cm −2 . To further investigate the kinetic characteristics of the four sample electrodes, EIS was conducted at −0.20 V over a frequency range of 100 kHz to 100 mHz in 1 m KOH (Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
“…[50][51][52][53] Covalently incorporating functional organic moieties in a controllable manner onto the POMs surfaces make the precursor structure versatility more accessible. [57] Herein, we propose that the amount of nitrogen incorporations into Mo 2 C structure could be well controlled by using various organoimido-derivatized POMs with inherent MoN bonds as precursors (Scheme 1). [54][55][56] Recent work by our group has demonstrated that organoimido-derivatized POM clusters with arylamine ligands and phenylphosphonic acid ligands can function as the molybdenum, carbon, nitrogen, and phosphorus sources, and in situ carbonization will result in the formation of Mo 2 C and MoP hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…As revealed by the charge transfer resistance ( R ct ) in Table , the NiCo‐POM/Ni electrode displayed the R ct of 11.9 Ω, which was lower than those of NiMn‐POM/Ni (12.6 Ω), NiZn‐POM/Ni (15.1 Ω) and Ni‐POM/Ni (13.6 Ω). This result indicated that the NiCo‐POM/Ni possessed the lowest charge‐transfer resistance and superior conductivity, which enabled efficient interfacial electron transport without a binder or conductive additive for HER . To rationalize whether this finding was correlated to the electrochemically active surface areas (ECSA) of the electrodes, the ECSA values was determined based on the double‐layer capacitance ( C dl ) calculated from voltammetric data in the non‐faradaic region.…”
Section: Resultsmentioning
confidence: 99%